PENGARUH MARKETING MIX TERHADAP KEPUTUSAN KONSUMEN UNTUK ME-NABUNG PADA BANK PERKREDITAN RAKYAT PRISMA DANA AIRMADIDI KABU-PATEN MINAHASA UTARA - Charles R. Ngangi (Sam Ratulangi University, 2012)
This study aimed to analyze the effect of marketing mix variables (product, price, promotion, and place) to the consumer's decision to save the Rural Bank Prisma Airmadidi Fund. The research was conducted in November to December 2010. The primary data obtained through interviews with 50 respondents, customers using questionnaire. Analysis using multiple linear regression with SPSS version 17.0. Hypothesis testing using test-f, t-test, and the coefficient of determination (R2).The results showed that all four marketing mix variables jointly influence consumer decisions. Variable products and variable space has a positive and significant influence on consumer decisions, promotion variables have positive but not significant, while the price variable and no significant negative effect on consumer decisions. RB Prism Fund is expected to remain maintain product quality while expanding the market to increase the number of consumers / customers. The interest rate should be above the savings rate savings banks. Promotion strategies are needed in the form of prizes to increase the number of BPR Prism Funds.Keywords: marketing mix, decision to save